Meningkatkan aktifitas dan hasil belajar fisika melalui penerapan model pembelajaran siklus belajar hipotetik-deduktif - I Made Sudana (Indonesian Journal of Educational Development, 2020)
This study is a classroom action research, which aimed to determine the effectiveness of the Hypothetic-Deductive Learning Cycle Learning Model to improve students’ learning activities and outcomes in Physics subjects. The research subjects were 36 students’ of class X-MIPA3 of SMA Negeri 4 Denpasar in the academic year 2015/2016. The object of this research is the activities and learning outcomes of students' physics on the subject matter of Irregular Straight Motion and Irregularly Changed Straight Motion. Student learning activity data was collected using observation, while Physics student learning outcomes data was collected using tests. The criteria for success of this study are set as follows: (1) student activity is at least an active category, (2) the average student learning outcomes are at least 76, and (3) classical learning completion is at least 85%. The data obtained were analyzed descriptively qualitatively. At the end of the second cycle, the results of the study showed that: (1) the activities of students were classified as active, (2) the average student learning outcomes reached 79.50 and (3) classical learning completeness reached 88.89%. Conclusion, the Hypothetical-Deductive Learning Cycle Learning Model effectively improves the activities and learning outcomes of students’ of class X-MIPA3 of SMA Negeri 4 Denpasar in the academic year 2015/2016. Penelitian ini merupakan penelitian tindakan kelas, bertujuan untuk mengetahui efektivitas Model Pembelajaran Siklus Belajar Hipotetik-Deduktif sebagai upaya untuk meningkatkan aktivitas dan hasil belajar siswa pada mata pelajaran Fisika. Subjek penelitian adalah siswa kelas X-MIPA3 SMA Negeri 4 Denpasar yang berjumlah 36 orang pada tahun pelajaran 2015/2016. Objek penelitian ini adalah aktivitas dan hasil belajar Fisika siswa pada materi pelajaran Gerak Lurus Beraturan (GLB) dan Gerak Lurus Berubah Beraturan (GLBB). Data aktivitas belajar siswa dikumpulkan menggunakan lembar observasi, sedangkan data hasil belajar Fisika siswa dikumpulkan menggunakan tes hasil belajar. Kriteria keberhasilan penelitian ini ditetapkan sebagai berikut: (1 aktivitas siswa minimal kategori aktif, (2) rerata hasil belajar siswa minimal 76, dan (3) Ketuntasan Belajar Klasikal minimal 85%. Data yang diperoleh dianalisis secara deskriptif kualitatif. Pada akhir siklus II, hasil penelitian menunjukkan bahwa: (1) aktivitas siswa tergolong kategori aktif, (2) rerata hasil belajar siswa mencapai 79,50 dan (3) ketuntasan belajar mencapai 88,89%. Kesimpulan, Model Pembelajaran Siklus Belajar Hipotetik-Deduktif efektif meningkatkan aktivitas dan hasil belajar siswa kelas X-MIPA3 SMA Negeri 4 Denpasar pada tahun pelajaran 2015/2016.